CONTENT VALIDITY AND RELIABILITY ANALYSIS OF INTEGRATED ISLAMIC-SCIENCE TEST INSTRUMENT TO MEASURE THE STUDENT’S CRITICAL THINKING ABILITY - Muhammad Fajrul Bahri; Supahar Supahar (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
This research is aimed to asses the validity and reliability of Islamic-science integrated test instrument. The instrument was formed in multiple-choice test instrument which is regarded as appropriate to assist student critical thinking ability. The validity of the instrument and its reliability were assessed quantitively. While Aiken’s V was used for assessing content validity, and Alpa Cronbach was used for assessing content reliability. In terms of Item Response Theory, it was assessed through the test I Function information and Standard Error of Measurement (SEM). The result of developing Islamic-science integrated test instrument to measure critical thinking ability was formed in the form of closed-minded multiple choice that consisting of two test packages. The total test items on the instrument are 45 items consisting of 25 items with 5 shared items (anchor). Estimation of the validity test instrument obtained an index ranging from 0.75 to 1. According to classical test theory, the coefficient of reliability was 0.70 and according to the total function information and Standart Error of Measurement, the test instrument was suitable for rangeability from 1.75 to +3. Thus, the test instrument is proved reliable and valid. A total of seven teachers using the declared that the test instrument is appropriate to use in measuring learning outcomes, especially the critical thinking abilities of the student Penelitian ini bertujuan untuk menganalisis konten validitas dan reliabilitas dari intrumen tes terintegrasi agama dan sains. Konten validitas dan reliabilitas dianalisis secara kuantitatif. Pendekatan kuantitatif untuk konten validitas menggunakan Aiken’s V, sedangkan untuk konten reliabilitas menggunakan Alpha Cronbach dan secara teori respon butir menggunakan fungsi informasi dan kesalahan pengukuran. Hasil pengembangan berupa instrumen tes terintegrasi agama dan sains untuk mengukur kemampuan berpikir kritis berupa tes pilihan ganda beralasan tertutup yang terdiri atas dua paket tes. Total item tes pada instrumen sebanyak 45 item yang terdiri dari 25 item dengan 5 item bersama (anchor). Estimasi validitas instrumen tes menggunakan formula Aiken diperoleh rentang indeks antara 0,75 sampai 1. Estimasi reliabilitas tes menurut teori tes klasik ditunjukkan oleh koefisien Alpha Cronbach sebesar 0,70 dan menurut kurva total fungsi informasi dan SEM yang berdasar pada teori respon butir (IRT) instrumen tes cocok untuk rentang kemampuan -1,75 sampai +3. Dengan demikian instrumen tes terbukti valid dan reliabel. Sejumlah tujuh guru pengguna instrumen tes menyatakan bahwa instrumen tes layak digunakan dalam pembelajaran. Dengan demikian instrumen tes cocok dan layak digunakan untuk mengukur hasil pembelajaran khususnya pada kemampuan berpikir kritis peserta didik.